2020
DOI: 10.1007/s11930-020-00263-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Desire and Fantasies in the LGBT+ Community: Focus on Lesbian Women and Gay Men

Abstract: Purpose of Review The purpose of this review is to summarize the current knowledge around sexual desire, fantasies, and related biopsychosocial factors that may facilitate or obstruct sexual expressions in lesbian women and gay men. Recent Findings Sexual desire levels and related problems do not seem significantly different in people who identify as gay or lesbian compared to their heterosexual counterparts. Evidence has shown lesbian women and gay men may have specific desire expressions and biopsychosocial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 97 publications
(122 reference statements)
2
27
1
Order By: Relevance
“…These findings are in line with other studies highlighting lower levels of sexual desire reported by MtF and higher levels reported by FtM after gender-confirming interventions [26][27][28][29]. However, sexual desire variation after GAS is not always perceived as distressful for trans people as many reported it as a "desired" effect, perceiving it as the "typical" expression of their gender identity and role [28,30]. Conversely, it should be noted that the will to adhere to stereotypic gender roles of the identified gender may also influence the expression of sexual desire and behavior in transgender people.…”
Section: Transgender Women and Mensupporting
confidence: 93%
See 4 more Smart Citations
“…These findings are in line with other studies highlighting lower levels of sexual desire reported by MtF and higher levels reported by FtM after gender-confirming interventions [26][27][28][29]. However, sexual desire variation after GAS is not always perceived as distressful for trans people as many reported it as a "desired" effect, perceiving it as the "typical" expression of their gender identity and role [28,30]. Conversely, it should be noted that the will to adhere to stereotypic gender roles of the identified gender may also influence the expression of sexual desire and behavior in transgender people.…”
Section: Transgender Women and Mensupporting
confidence: 93%
“…Currently, there is no evidence to confirm a direct positive association between testosterone levels and sexual desire in FtM [25]. These findings are in line with other studies highlighting lower levels of sexual desire reported by MtF and higher levels reported by FtM after gender-confirming interventions [26][27][28][29]. However, sexual desire variation after GAS is not always perceived as distressful for trans people as many reported it as a "desired" effect, perceiving it as the "typical" expression of their gender identity and role [28,30].…”
Section: Transgender Women and Mensupporting
confidence: 63%
See 3 more Smart Citations